Silicon-based composite material, preparation method thereof and negative electrode

By using a porous matrix to load silicon nanoparticles in lithium-ion batteries and introducing heteroatoms to separate silicon nanoparticles, the problem of volume expansion of silicon-based composite materials during charging and discharging is solved, and the cyclic stability and mechanical strength of the electrode are improved.

CN119581506AActive Publication Date: 2025-03-07LANXI ZHIDE ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202311148345.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

Silicon-based composite materials produce large volume expansion during the charging and discharging of lithium-ion batteries, resulting in damage to the electrode structure, attenuation of battery capacity and reduced circulation efficiency.

Method used

Porous substrates are used as substrate materials to load silicon nanoparticles and heteroatoms are introduced to separate and bind silicon nanoparticles, controlling the size and distribution of silicon material in the pores, thereby alleviating the volume expansion effect.

Benefits of technology

Effectively prevent structural collapse caused by expansion of silicon-embedded lithium, improve the cyclic stability of the electrode, and improve the mechanical strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581506A_ABST
    Figure CN119581506A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-based composite material, a preparation method thereof and a negative electrode. The silicon composite material comprises a porous matrix, silicon nanoparticles and heteroatoms, the porous matrix is provided with a three-dimensional cross pore channel with multistage pore diameters, the pore channel contains at least one silicon nanoparticle, the heteroatoms at least partially coat the surfaces of the silicon nanoparticles, and / or the heteroatoms are spaced among the silicon nanoparticles. According to the silicon-based composite material provided by the invention, the porous matrix is adopted as a substrate material to load the silicon nanoparticles and the heteroatoms doped in the silicon nanoparticles, and the silicon nanoparticles are separated and bound by doping the heteroatoms in the silicon nanoparticles, so that the size and distribution of the silicon material in pore channels are controlled; the silicon material is uniformly dispersed in the three-dimensional crossed pore channels of the porous matrix, so that the volume effect of silicon in the charging and discharging process is effectively relieved, the collapse of the composite material structure caused by the expansion of lithium-intercalated silicon is prevented, and the cycling stability of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a silicon-based composite material, a preparation method thereof, and a negative electrode. Background Art

[0002] Silicon is an alloyed lithium-intercalation material with a theoretical lithium-intercalation capacity of up to 4200mAh / g. It is abundant in resources, safe and non-toxic, and is currently the most promising negative electrode material for lithium-ion batteries to replace traditional carbon negative electrodes and achieve industrial application. There are two problems with silicon-based materials as negative electrode materials for lithium-ion batteries. First, silicon has poor conductivity, which can be solved by various methods such as carbon carriers, carbon blending, and carbon coating; second, silicon will produce huge volume expansion / contraction during the lithium insertion / de-lithiation process, which will lead to damage to the electrode structure, battery capacity attenuation, and reduced cycle efficiency.

[0003] In recent years, by optimizing silicon particle size, distribution and adjusting the structure of negative electrode materials, the volume expansion of silicon-based composite materials such as silicon-oxygen negative electrode materials and silicon-carbon negative electrode materials has been greatly reduced. However, this improvement is far from enough for practical applications. Therefore, how to further reduce the volume expansion of silicon-based composite materials during charging and discharging and improve the cycle life is an important issue that needs to be solved urgently. Summary of the invention

[0004] The main purpose of the present invention is to provide a silicon-based composite material and a preparation method and a negative electrode thereof, so as to solve the problem in the prior art that silicon as a negative electrode material for lithium-ion batteries produces a large volume expansion during the charge and discharge process, resulting in a shortened cycle life.

[0005] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a silicon-based composite material is provided, wherein the silicon-based composite material comprises silicon-based composite material particles, wherein the silicon-based composite material particles comprise a porous matrix, silicon nanoparticles and heteroatoms, wherein the porous matrix has three-dimensional cross-channels comprising multi-level pore sizes, wherein the channels contain at least one silicon nanoparticle, wherein the heteroatoms are at least partially coated on the surface of the silicon nanoparticles, and / or wherein the heteroatoms are spaced between the silicon nanoparticles.

[0006] Furthermore, the silicon-based composite material also contains closed pores, and the closed pore volume of the silicon-based composite material is 0.01 to 0.25 cm 3 / g; and / or the true density of the silicon-based negative electrode material is 1.3 to 3.0 g / cm 3 .

[0007] Furthermore, the specific surface area of ​​the silicon-based composite material is 0.5 to 50 m 2 / g, preferably 0.5 to 10 m 2 / g, more preferably 0.5 to 2 m2 / g; and / or, the compacted specific surface area of ​​the silicon-based composite material (silicon-based composite material at 4000 kgf / cm 2 The specific surface area of ​​the material after compaction under pressure is 1 to 20 times, preferably 1 to 10 times, and more preferably 1 to 5 times the specific surface area of ​​the silicon-based composite material.

[0008] Further, the silicon nanoparticles include first silicon nanoparticles, second silicon nanoparticles and third silicon nanoparticles, the size of the first silicon nanoparticles is D1, 0.35nm≤D1<2nm, the size of the second silicon nanoparticles is D2, 2nm≤D2<5nm, and the size of the third silicon nanoparticles is D3, 5nm≤D3≤10nm. Further, based on the mass of the silicon nanoparticles, the mass content of the first silicon nanoparticles is 60-100%, the mass content of the second silicon nanoparticles is 0-40%, and the mass content of the third silicon nanoparticles is 0-5%.

[0009] Furthermore, the pores of the porous matrix include a first pore, a second pore and a third pore. The pore size of the first pore is d1, 0.35nm≤d1≤2nm, the pore size of the second pore is d2, 2nm<d2≤10nm, and the pore size of the third pore is d3, 10nm<d3≤50nm. Furthermore, the volume proportion of the first pore in the porous matrix pore is 30-95%, the volume proportion of the second pore in the porous matrix pore is 1-60%, and the volume proportion of the third pore in the porous matrix pore is 0-15%. Furthermore, the porous matrix includes at least one of porous carbon, porous metal skeleton, porous metal oxide skeleton, porous metal organic skeleton, and porous organic-inorganic hybrid material skeleton; the specific surface area of ​​the porous matrix is ​​200-3000m 2 / g, pore volume is 0.2~3.0cm 3 / g.

[0010] Furthermore, in the silicon-based composite material, the mass content of silicon element is 5 to 90%, and the mass content of heteroatoms is 0.1 to 10%. Furthermore, the heteroatoms are coated on the surface of silicon nanoparticles and / or spaced between multiple silicon nanoparticles to form a heteroatom layer, and the total thickness of the heteroatom layer is 0.5 to 50 nm, preferably 0.5 to 10 nm, and more preferably 0.5 to 2 nm.

[0011] Furthermore, the heteroatom includes at least one of B, C, N, P, O, and S.

[0012] Furthermore, the median particle size d of the silicon-based composite material V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / d V,50is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 0.8 to 1.2. Further, the silicon-based negative electrode material further comprises a coating layer, preferably, the material of the coating layer is selected from one or more of a solid electrolyte, a conductive polymer, a carbonaceous material, a metal, an alloy, a metal oxide, a metal hydroxide, a metal halide, a metal sulfide, a metal phosphate, a boric acid compound, a sulfuric acid compound, a nitric acid compound, a polymetallic oxyacid salt, etc.; further preferably, the coating layer comprises a carbonaceous material.

[0013] In order to achieve the above-mentioned object, according to the second aspect of the present invention, a method for preparing a silicon-based composite material is also provided, the method comprising: step S1, providing a porous matrix, the porous matrix having three-dimensional cross-channels with multi-level apertures; step S2, contacting a silicon-containing precursor and a heteroatom-containing precursor with the porous matrix to obtain a silicon-based composite material; wherein the porous matrix, the channel, the silicon nanoparticles and the heteroatom respectively have the same meanings as the corresponding concepts in the first aspect above. Further, in step S2, the silicon-containing precursor includes at least one of monosilane, disilane, trisilane, halosilane, polysilane, thiorrole and its derivatives, silanol and its derivatives; the heteroatom-containing precursor includes at least one of an oxygen-containing precursor, a carbon-containing precursor, a nitrogen-containing precursor, a phosphorus-containing precursor, a sulfur-containing precursor or a boron-containing precursor.

[0014] Furthermore, in step S2, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor contact the porous matrix is ​​150-1000°C for 0.1-100h; further, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor contact the porous matrix is ​​200-700°C.

[0015] Furthermore, in step S2, the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix in the following manners: the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix alternately; or, the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix simultaneously; or, the silicon-containing precursor and a mixed gas comprising the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix alternately. Preferably, the silicon-containing precursor is continuously contacted with the porous matrix, and the heteroatom-containing precursor is intermittently introduced during this process.

[0016] Furthermore, the method for preparing the silicon-based composite material further comprises a step S3 arranged after the step S2, of performing a coating treatment to form a coating layer; wherein the coating layer has the same meaning as the coating layer in the first aspect above.

[0017] According to a third aspect of the present invention, a negative electrode is provided, which comprises a negative electrode active material, wherein the negative electrode active material comprises the silicon-based negative electrode material provided by the first aspect or the silicon-based composite material obtained according to the preparation method provided by the second aspect.

[0018] According to a third aspect of the present invention, a battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the silicon-based negative electrode material provided in the first aspect above or a silicon-based composite material obtained according to the preparation method provided in the second aspect above.

[0019] By applying the technical solution of the present application, the silicon-based composite material provided by the present application adopts a porous matrix as a base material to load silicon nanoparticles, and introduces heteroatoms to further limit the size of the silicon nanoparticles, separate and constrain the silicon nanoparticles, and control the size and distribution of the silicon material in the pores, so that the silicon material is evenly dispersed in the three-dimensional cross-pores of the porous matrix, effectively alleviating the volume effect of silicon during the charging and discharging process, preventing the expansion of silicon embedded with lithium from causing the collapse of the composite material structure, and improving the cycle stability of the electrode.

[0020] At the same time, the strong Si-X bond (X is a heteroatom) between heteroatoms and silicon nanoparticles can restrain the expansion of silicon-embedded lithium, or transfer the stress of silicon-embedded lithium to the surrounding space (such as porous matrix, etc.), such as a small amount of closed pores adjacent to silicon nanoparticles as buffer space, thereby further improving the cycle stability of negative electrode materials. In addition, the silicon-based composite material has a dense structure and excellent mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1 A schematic diagram of the cross-sectional structure of the silicon-based composite material provided by the present application is shown;

[0023] Figure 2 A schematic diagram showing the structure of a porous matrix in a silicon-based composite material provided in the present application is shown;

[0024] Figure 3 shows the pore size distribution diagram of the porous matrix in Example 1;

[0025] Figure 4 The XRD pattern of the silicon-based composite material obtained in Example 1 is shown;

[0026] Figure 5The dQ / dV curve obtained from the delithiation curve of the first cycle in the constant current charge and discharge curve of a lithium electronic battery according to the silicon-based composite material obtained in Example 1 is shown;

[0027] Figure 6 The dQ / dV curve obtained from the delithiation curve of the first cycle in the constant current charge and discharge curve of a lithium electronic battery according to the silicon-based composite material obtained in Comparative Example 1 is shown. DETAILED DESCRIPTION

[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0029] As analyzed in the background technology of this application, in the prior art, silicon as a negative electrode material for lithium-ion batteries produces a large volume expansion during the charging and discharging process. In order to solve this problem, CN108475779B discloses a new material with extremely durable lithium embedding and a method for manufacturing the same, comprising a composite of a porous carbon support and silicon. The porous support material may be a carbon material containing micropores, mesopores and / or macropores, and its pores are subsequently filled with silicon. Silicon is deposited in the pore structure of the porous support material to form a composite. These composites exhibit significant and durable lithium embedding capabilities. After being prepared into a battery cell, it has an excellent cycle life. The invention deposits silicon into the pores of the porous carbon material by chemical vapor deposition to form uniformly dispersed nano-silicon particles, which can reduce the expansion of the silicon negative electrode material itself to a certain extent. The improvement in electrochemical performance is highly correlated with the size and distribution of the deposited silicon particles and the physicochemical properties of the support material. Compared with graphite anode, the silicon material deposited by this technology will still expand greatly during the cycle process; at the same time, because the pore size distribution of the porous carbon support used in this technology is relatively wide, the larger pores are difficult to close during the silicon deposition process, which increases the probability of contact between the deposited silicon in the composite material and the electrolyte, and more side reactions occur during the cycle, and more SEI is produced, which also has a certain impact on the life. Therefore, it is necessary to further reduce the expansion of the composite material itself and improve the cycle life by continuously optimizing the structure of the composite material.

[0030] In order to further optimize the structure of the silicon-based composite material, reduce volume expansion and increase cycle life, the present application provides a silicon-based composite material.

[0031] A. Silicon-based composite material In a typical embodiment of the present application, a silicon-based composite material is provided, wherein the silicon-based composite material comprises silicon-based composite material particles, such as Figure 1As shown, the silicon-based composite material particles include a porous matrix, silicon nanoparticles and heteroatoms; the pores of the porous matrix contain at least one silicon nanoparticle, the heteroatoms are at least partially coated on the surface of the silicon nanoparticles, and / or the heteroatoms are spaced between the silicon nanoparticles; Figure 2 As shown, the porous matrix has three-dimensional intersecting channels with multiple levels of pore sizes.

[0032] In the present application, “the pores contain at least one silicon nanoparticle” means that some pores with smaller diameters are filled with only one silicon nanoparticle, and some pores with larger diameters contain multiple silicon nanoparticles.

[0033] By applying the technical solution of the present application, the silicon-based composite material provided by the present application adopts a porous matrix as a base material to load silicon nanoparticles and heteroatoms doped in the silicon nanoparticles. The silicon nanoparticles are separated and bound by doping heteroatoms into the silicon nanoparticles, and the size and distribution of the silicon material in the pores are controlled, so that the silicon material is uniformly dispersed in the three-dimensional cross-pores of the porous matrix, which effectively alleviates the volume effect of silicon during the charging and discharging process, prevents the expansion of silicon embedded with lithium and causes the collapse of the composite material structure, and improves the cycle stability of the electrode.

[0034] At the same time, the strong Si-X bond (X is a heteroatom) between the heteroatom and the silicon nanoparticles can restrain the expansion of silicon-embedded lithium, or transfer the stress of silicon-embedded lithium to the surrounding medium such as the porous matrix, thereby improving the cycle stability of the negative electrode material. In addition, the strong Si-X bond can also improve the mechanical strength of the silicon-based composite material, thereby further improving the structural stability of the material.

[0035] In order to further alleviate the expansion of silicon nanoparticles embedded with lithium and improve the cyclic stability of the above-mentioned silicon-based composite materials, preferably, the silicon-based composite material also contains closed pores. In some embodiments, closed pores exist inside the porous matrix; in some embodiments, the porous matrix can accommodate pores for the entry of silicon-containing precursor molecules, which are filled by silicon nanoparticles or a collection of silicon nanoparticles and heteroatoms after the deposition is completed, and sometimes new closed pores are formed. Among them, this type of closed pores is usually located near silicon nanoparticles. In particular, a small number of closed pores adjacent to silicon nanoparticles can serve as a buffer space for the expansion of silicon embedded with lithium, preventing the silicon particles from expanding and rupturing, and improving the cyclic stability of the material. However, the amount of closed pores in the composite material should not be too much. Excessive pores in the material will lead to a decrease in the strength of the material. During the compaction of the pole piece, it is easy to crush to form a large number of open pores, increase the specific surface, and reduce the first effect; and the residual pores still lead to a decrease in the strength of the material in the later stage, forming a stress weak point in the cycle process, resulting in a decrease in the cyclic stability of the material.

[0036] Due to the presence of closed pores, the skeleton density of silicon-based composite materials is lower than the theoretical density of non-porous pure silicon and pure matrix materials (such as graphite). According to information available to those skilled in the art, the theoretical density of pure silicon material is 2.33 g / cm 3 The theoretical density of graphite material is 2.09~2.33g / cm 3 The theoretical density of alumina can reach 3.50g / cm 3 . The volume of closed pores enclosed in the material can be calculated from the skeleton density and theoretical density. The skeleton density of the material is usually obtained by helium pycnometry. In this article, the skeleton density of the material obtained by helium pycnometry is called the true density of the material. The closed-pore volume is calculated by subtracting the volume of the corresponding completely dense material composed of the same elements from the skeleton volume of the composite material, wherein the skeleton volume of the composite material is the reciprocal of the true density of the composite material; the skeleton volume consists of two parts, one part is the volume of the corresponding completely dense material composed of the same elements, and the other part is the closed-pore volume; the volume of the completely dense material is the reciprocal of its true density (that is, the theoretical density of the completely dense material composed of the same elements). In some embodiments, the closed-pore volume of the silicon-based composite material is 0.01 to 0.25 cm 3 / g; In some embodiments, the true density of the silicon-based composite material obtained by helium specific gravity method is 1.3-3.0 g / cm 3 .

[0037] The silicon-based composite material comprises silicon-based composite material particles. The silicon-based composite material particles have a suitable particle size distribution to meet their application requirements. In addition, the particle size distribution should be as uniform as possible. In some embodiments, the median particle size d of the silicon-based composite material is V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.8~1.2.

[0038] [Porous matrix]

[0039] The type of the above-mentioned porous matrix is ​​not specifically limited, and any commonly used porous material for negative electrode materials can be used, including but not limited to porous carbon, porous metal skeleton (such as foamed copper), porous oxide skeleton (such as porous titanium oxide, porous aluminum oxide), porous metal organic skeleton (such as metal organic skeleton MOF, zeolite imidazolate skeleton ZIF), porous organic-inorganic hybrid material (such as porous polyvinyl alcohol PVA / SiO2 hybrid material) skeletons, any one or a composite skeleton formed by two or more thereof. The porous matrix should have a large specific surface area and rich pore structure to provide sites and spaces for the deposition of silicon nanoparticles. The specific surface area and pore distribution of the porous matrix directly affect the silicon deposition effect, and then affect the specific surface area of ​​the composite material and the size of the silicon nanoparticles in the composite material.

[0040] In some embodiments, the specific surface area of ​​the porous matrix is ​​200 to 3000 m 2 / g, pore volume is 0.2~3.0cm 3 / g. For example, the specific surface area of ​​the porous matrix can be 200m 2 / g、500m 2 / g、800m 2 / g、1000m 2 / g、1500m 2 / g, 2000m 2 / g、2500m 2 / g、3000m 2 / g or the range between any two values; the pore volume can be 0.2cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1.0cm 3 / g, 1.5cm 3 / g, 2.0cm 3 / g, 2.5cm 3 / g, 3.0cm 3 In some preferred embodiments, the specific surface area of ​​the porous matrix is ​​1000-2000 m 2 / g, pore volume is 0.5~1.0cm 3 / g.

[0041] In some embodiments, the porous matrix is ​​porous carbon, which can be prepared from a carbon precursor by pyrolysis and / or activation process. The carbon precursor includes one or more of a polymer precursor, a biomass precursor and a fossil carbon source. For example, the carbon precursor may be, but is not limited to, one or more of glucose, sucrose, maltose, lactose, cyclodextrin, starch, glycogen, cellulose, hemicellulose, lignin, epoxy resin, thermoplastic phenolic resin, thermosetting phenolic resin, polyoxymethylene resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, coconut shell, rice shell, and wood. In some embodiments, the pyrolysis temperature is 500 to 1800°C, and the pyrolysis time is 0.5 to 10 hours. The pyrolysis temperature and pyrolysis time can vary, for example, the pyrolysis temperature can be 650-950°C, 900-1100°C, 1050-1250°C, 1200-1400°C, 1350-1550°C or 1500-1750°C, etc.; the pyrolysis time can be 1-2h, 1.5-3h, 2-5h, 4-8h, 5-10h, etc. Activating the pyrolyzed carbon material is a common way to further adjust the porous carbon pore structure. The activation is usually achieved by contacting the pyrolyzed carbon material with an oxygen-containing substance, and the oxygen-containing substance includes but is not limited to KOH, NaOH, K2CO3, Na2CO3, H3PO4, H2O, CO2, O2, etc.; the contact method can be liquid-solid contact or gas-solid contact; the contact temperature is 400-1200°C. In some typical embodiments, the porous carbon material is prepared according to the following steps: the carbon precursor is heated to 800°C at a heating rate of 2°C / min in a N2 atmosphere and maintained for 2 hours, and then heated to 900°C in a mixture of CO2 and N2 and maintained for 2 hours to obtain a porous carbon material. The specific surface area and pore volume of the porous carbon can be adjusted by the heating rate, the insulation temperature and time. In addition, heteroatoms can be introduced into the carbon precursor to prepare a porous carbon material containing heteroatoms.

[0042] In some embodiments, the above-mentioned porous metal skeleton, porous oxide skeleton, porous metal-organic skeleton, and porous organic-inorganic hybrid material can be selected from commercial specification products, or prepared by methods known in the art, such as hydrothermal method, solvothermal method, electrochemical deposition method, powder metallurgy method, molten metal method, and ion exchange method, and the pore size and proportion of the porous skeleton can be adjusted by controlling the process parameters.

[0043] [Pore structure of porous matrix]

[0044] The pores of the porous matrix are the places where silicon nanoparticles are deposited. The pores of the porous matrix determine the upper limit of the size of silicon nanoparticles and the collection of silicon nanoparticles and heteroatoms, and the distribution of the pores determines the distribution of silicon nanoparticles in silicon-based composite materials. On the other hand, as the base material of silicon-based composite materials, the pore structure of the porous matrix also greatly affects the structural stability of the composite material. Figure 1 As shown, the present application specially designs a pore network structure with multi-level pores connected to each other for the porous matrix, and imposes certain restrictions on its pore size distribution. The design principle of the multi-level pore size feature of the substrate material, that is, including different pore sizes in a specific proportion, is to better control the size and distribution of the silicon nanomaterial.

[0045] In some embodiments, the pore size of the porous substrate is divided into three different size ranges, corresponding to the deposition areas of different forms of silicon nanoparticles or a collection of silicon nanoparticles and heteroatom layers. The pores of the above-mentioned porous matrix include a first pore, a second pore and a third pore. The pore size of the first pore is d1, 0.35≤d1≤2nm, the pore size of the second pore is d2, 2<d2≤10nm, and the pore size of the third pore is d3, 10<d3≤50nm. When the silicon-containing precursor enters the first pore with a smaller size, it decomposes in the pore to form silicon nanoparticles. Optionally, due to different deposition conditions, closed pores may be left in the first pore. The presence of an appropriate amount of closed pores can provide a buffer space for the volume expansion of silicon embedded lithium and reduce the expansion rate of the pole piece. The second pore size is relatively large, and the continuous deposition of silicon-containing precursors in the pores will produce larger silicon nanoparticles. However, the larger silicon nanoparticles will undergo a large volume change during the charge and discharge cycle of the lithium-ion battery, resulting in repeated destruction and regeneration of the SEI. Moreover, this volume change makes the silicon particles very easy to break or even pulverize, causing the silicon particles to lose electrical contact and fail, and the battery capacity continues to decrease. Therefore, for larger pores, it is necessary to introduce heteroatom-containing precursors at the same time as the silicon nanoparticles are deposited and / or in the gaps. The heteroatom-containing substances formed by decomposition further separate the silicon nanoparticles in the larger pores to ensure that the formed silicon nanoparticles are all of smaller size.

[0046] According to the IUPAC classification of material pore size, the first channel is a micropore, and the second and third channels are mesopores. If the porous matrix contains only micropores, the silicon-containing precursor is easily blocked at the pore mouth during migration in the channel, and the silicon-containing precursor in the subsequent deposition process can no longer enter the channel for deposition but deposits on the outer surface of the substrate material, which will lead to excessive closed pores and silicon-rich surface of the material. Although too many closed pores will reduce the expansion rate of the material's pole piece, it will lead to a decrease in the structural stability of the composite material; the silicon-rich surface of the material is easy to form larger silicon particles on the surface, and the cycle stability is poor. On the other hand, if the porous matrix contains too much mesopores, the deposition process can be controlled to form a collection of silicon nanoparticles-heteroatom layers in the pores of the substrate material, but on the one hand, the substrate material containing only mesopores needs to be prepared using expensive organic templates or hard template methods, and the cost of the substrate material is high; on the other hand, more mesopores mean that more heteroatom layers are needed to separate silicon nanoparticles, the heteroatom content in the composite material is increased, and the silicon element content with high reversible lithium insertion capacity is reduced, and the material specific capacity and first efficiency are reduced. Therefore, a certain amount of micropores and mesopores are required in the pore size distribution of the porous matrix, and the mesopore size should not be too large. In some embodiments, the volume proportion of the first channel in the porous matrix channel is 30-95% (such as 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% or a range between any two values), the volume proportion of the second channel in the porous matrix channel is 1-60% (such as 1%, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60% or a range between any two values), and the volume proportion of the third channel in the porous matrix channel is 0-15% (such as 0%, 2%, 5%, 7%, 10%, 12%, 15% or a range between any two values). The multi-level channel size and distribution of the porous matrix are within the above range, and the silicon-based composite material has better electrical properties and cycle stability.

[0047] The pore size and distribution of the porous matrix can be tested by gas adsorption such as N2 adsorption, CO2 adsorption, Ar adsorption, etc. on the porous matrix before the deposition of the silicon-containing precursor. The pore distribution information can be obtained by simulating the adsorption isotherm. For silicon-based composite materials, they can be digested in HF to remove Si in the composite material, and the porous carbon material obtained by digestion can be tested for gas adsorption and pore distribution analysis.

[0048] In summary, the multi-level pore structure of the porous matrix has two functions. First, during the deposition of silicon-containing precursors or silicon-containing precursors and heteroatom-containing precursors, the multi-level pore characteristics of the substrate material are conducive to the transport of substances and energy (heat) during the siliconization process and the formation of controllable silicon particle size. Second, in the resulting silicon-based composite material, silicon nanoparticles, or a collection of silicon nanoparticles and heteroatom layers, are separated by the substrate material to form a dense structure, and the mechanical strength of the composite material is improved. The substrate material constrains and separates silicon nanoparticles, which can alleviate the lithium-embedded expansion of silicon nanoparticles; a small amount of closed pores adjacent to silicon nanoparticles can serve as a buffer space for expansion, and the graphite-like layers of carbon materials can also provide buffer space by reducing interlayer spacing or shifting stacking faults.

[0049] [Silicon Nanoparticles]

[0050] Nano-sizing of silicon particles is the most important means to inhibit the expansion of silicon embedded with lithium. Silicon nanoparticles with larger sizes will undergo large volume changes during the charge and discharge cycle of lithium-ion batteries, resulting in repeated destruction and regeneration of SEI, and this volume change makes the silicon particles very easy to break or even pulverize, causing the silicon particles to lose electrical contact and fail, and the battery capacity continues to decrease. On a porous matrix with controllable pore size, controllable deposition of silicon nanoparticles is carried out. The maximum size of the silicon nanoparticles is limited by the pore size of the porous matrix, which is incomparable to the formation of silicon-carbon composite materials by solid phase grinding of traditional silicon particles and carbon particles. As mentioned above, in order to inhibit the expansion of silicon embedded with lithium and improve the cyclic stability of silicon-based composite materials in lithium-ion batteries, the silicon-based composite materials should have a sufficiently small particle size. In some embodiments, the size of the silicon nanoparticles is 0.35 to 10 nm. In some embodiments, according to the size of the silicon nanoparticles, the silicon nanoparticles in the silicon-based composite material can be divided into three types, including first silicon nanoparticles, second silicon nanoparticles and third silicon nanoparticles, wherein the size of the first silicon nanoparticles is D1, 0.35nm≤D1<2nm, the size of the second silicon nanoparticles is D2, 2nm≤D2<5nm, and the size of the third silicon nanoparticles is D3, 5nm≤D3≤10nm.

[0051] The size distribution of silicon nanoparticles can be controlled by controlling the pore size of the porous matrix and controllably introducing heteroatom layer deposition. The pore size of the porous matrix is ​​the first controlling factor of the size of silicon nanoparticles, and the size of silicon nanoparticles is not larger than the pore size of the porous matrix. For larger porous matrix pore sizes, the size of silicon nanoparticles directly obtained is larger, which is prone to cause large volume changes during the lithium insertion-delithiation cycle, causing the cycle performance to decrease. Therefore, the present application introduces heteroatoms in the silicon deposition process or gaps to limit the excessive growth of silicon nanoparticles, thereby controlling the size of silicon nanoparticles within a certain range. The size of the collection of silicon nanoparticles and heteroatom layers is not larger than the pore size of the porous matrix. In some embodiments, the mass content of the first silicon nanoparticles in the silicon-based composite material is 65-100%, such as 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, 100% or a range between any two values, the mass content of the second silicon nanoparticles in the silicon nanoparticles is 0-30%, such as 0, 1%, 2%, 5%, 10%, 20%, 30% or a range between any two values, and the mass content of the third silicon nanoparticles in the silicon nanoparticles is 0-5%, such as 0, 1%, 2%, 3%, 4%, 5% or a range between any two values.

[0052] As mentioned above, the size of the silicon nanoparticles, or the size of the collection of silicon nanoparticles and heteroatom layers, is not greater than the pore size of the porous matrix. Since the size of silicon nanoparticles in the composite material is small and usually amorphous, conventional XRD tests show a broadened peak packet at the Si crystallization peak position, and the size information of the silicon nanoparticles cannot be obtained. High-resolution transmission electron microscopy (HRTEM) can observe the lattice fringes of silicon, so that the size of silicon nanoparticles can be calculated, but this characterization method can only see the local information of the particles and cannot quickly obtain the statistical distribution of silicon nanoparticles in the material.

[0053] In the experimental data of this application, it is found that by controlling the pore size of the porous matrix and the introduction of heteroatoms, silicon-based composite materials with different electrochemical performances can be obtained. In particular, when the proportion of micropores in the porous matrix is ​​large or there are more heteroatoms, there is basically no platform at 0.4-0.5V in the half-cell delithiation curve, showing an obvious slope-type delithiation curve; on the contrary, if the pore size of the porous matrix is ​​large and no heteroatom spacing is performed, a larger platform will appear at 0.4-0.5V in the half-cell delithiation curve. Obviously, the silicon nanoparticle size of the former is smaller than that of the latter, that is, the size of the silicon nanoparticles will ultimately be reflected in its electrochemical performance.

[0054] Silicon nanoparticles in silicon-based composite materials undergo amorphous to crystalline transformation under high temperature conditions, and further undergo grain growth, while the porous matrix in the composite material does not undergo significant changes under this treatment condition. Therefore, the present application treats the silicon-based composite material under N2 atmosphere at 800°C and performs XRD testing to analyze its silicon grain growth, which is called high-temperature XRD testing. The grain size after high-temperature treatment can be calculated from the half-peak width of the silicon crystallization peak, and the number of grains involved in crystallization can be inferred from the relative intensity of the silicon crystallization peak and the amorphous peak, thereby indirectly reflecting the proportion of silicon nanoparticles of different sizes in the silicon-based composite material.

[0055] The delithiation platform of the half-cell constant current charge and discharge curve can be obtained by normalizing the delithiation curve and then taking the derivative of the voltage to obtain the dQ / dV value. Combining the high-temperature XRD test results and the delithiation dQ / dV value, we can gain an understanding of the size of silicon nanoparticles in silicon-based composite materials. According to the previous analysis, the smaller the size of the silicon nanoparticles, the smaller the size of the silicon nanoparticles obtained by high-temperature XRD, the smaller the delithiation dQ / dV value, and the shorter or even non-existent delithiation platform.

[0056] The content of silicon determines the specific capacity of silicon-based composite materials. The higher the silicon content, the higher the specific capacity of lithium embedded in silicon-based composite materials. On the other hand, when the silicon content is too high, the uniform distribution and nano-size of silicon nanoparticles are difficult to achieve. The silicon-based composite materials lack sufficient supporting structures and conductive ion-conducting matrix, and the expansion of silicon embedded in lithium cannot be well buffered or restrained, and the material cycle stability is poor. Therefore, the silicon content in silicon-based composite materials should be controlled within an appropriate range. In some embodiments, based on the total mass of the silicon-based composite material, the content of silicon is 5 to 90%, such as 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or a range between any two values. Preferably, in some embodiments, when the content of silicon is 30 to 60%, the silicon-based composite material has better electrical properties.

[0057] [Heteroatom]

[0058] From the description of the porous matrix and its pore structure and silicon nanoparticles, it can be seen that a certain amount of micropores and mesopores are required in the pore size distribution of the porous matrix, and the size of the mesopores should not be too large; based on the multi-level pore size pore structure of the multi-level matrix, for the second and third pores with larger sizes, it is necessary to introduce heteroatom precursors at the same time and / or in the gaps when the silicon nanoparticles are deposited, and the heteroatom-containing substances formed by decomposition further separate the silicon nanoparticles to ensure that the formed silicon nanoparticles have a smaller size. On the other hand, a strong Si-O bond or Si-X bond will be formed between the heteroatom O or other heteroatom X and the silicon nanoparticles, which can improve the mechanical strength of the silicon-based composite material, restrain the expansion of silicon-embedded lithium, or transfer the stress of silicon-embedded lithium to the surrounding space, and improve the cycle stability of the silicon-based composite material in lithium-ion batteries.

[0059] In addition, by adjusting the deposition method, the heteroatom can also be located at the interface between the porous matrix and the silicon nanoparticles, which plays a role in separating the porous matrix and the silicon nanoparticles and improving the strength of the porous matrix. This type of heteroatom may also exist in the first pore of the porous matrix.

[0060] The so-called "heteroatom" refers specifically to the silicon nanoparticles in the pores of the porous matrix, and the heteroatom is an atom other than silicon. The specific types of the above heteroatoms are not limited, including but not limited to any one or more of B, C, N, P, O, and S. In particular, when the heteroatom is O, the silicon-based composite material has a more excellent ability to inhibit volume expansion. In some embodiments, the heteroatom is coated on the surface of the silicon nanoparticle to form a heteroatom layer, and the total thickness of the heteroatom layer is 0.5 to 50 nm, preferably 0.5 to 10 nm, and more preferably 0.5 to 2 nm (such as 0.5 nm, 0.8 nm, 1 nm, 1.5 nm, 2 nm or any value therebetween); or, the heteroatom is arranged between multiple silicon nanoparticles to form a collection of silicon nanoparticles and heteroatom layers, which exist inside the pores of the porous matrix.

[0061] As mentioned above, heteroatoms are necessary structural components in silicon-based composite materials, but if the heteroatom content is too high, the specific capacity and the first coulombic efficiency of the composite material will be reduced. In some embodiments, based on the total mass of the above silicon-based composite material, the heteroatom content is 0.1-10%, preferably, when the heteroatom content is 0.5-5%, the silicon-based composite material has higher comprehensive performance, such as having higher specific capacity, first efficiency and cycle stability at the same time.

[0062] The above-mentioned heteroatoms only refer to the silicon nanoparticles in the pores of the porous matrix, which are introduced during the silicon infiltration process of the carbon precursor and form a carbon-containing heteroatom layer between the silicon nanoparticles. Here, the carbon atoms are heteroatoms for the silicon nanoparticles. However, when the porous matrix is a carbon material, the content of the carbon heteroatoms between the silicon nanoparticles is not easily obtained by testing the composite material and can only be estimated by the total carbon mass in the silicon-based composite material and the mass of the porous carbon before silicon infiltration. On the other hand, when the porous matrix is an oxide, if oxygen atoms are selected to separate the silicon nanoparticles, the oxygen content as a heteroatom can also be estimated in a similar way; of course, the oxygen content in the matrix will also affect the capacity and initial efficiency of the composite material.

[0063] [Aggregate of silicon nanoparticles and heteroatoms]

[0064] As described above, in the pores of the porous matrix, while depositing silicon nanoparticles and / or introducing a heteroatom precursor into the gaps, the formed heteroatom-containing substance further separates the silicon nanoparticles, which can ensure that the formed silicon nanoparticles all have relatively small sizes. Therefore, in the second and third pores of the porous matrix, there is an aggregate of silicon nanoparticles and heteroatoms. In the aggregate of silicon nanoparticles and heteroatoms, the heteroatoms or heteroatom layers exist in the form of compounds of silicon and heteroatoms, and there is a gradient structure. For example, when the heteroatom is an oxygen atom, the oxygen atom layer exists in the form of SiO x (0 < x < 1) between the silicon nanoparticles, and there is a concentration gradient of oxygen atoms and silicon atoms in the oxygen atom layer. The closer to the silicon nanoparticles, the higher the concentration of silicon atoms and the lower the concentration of oxygen atoms; conversely, the farther from the silicon nanoparticles, the lower the concentration of silicon atoms and the higher the concentration of oxygen atoms. Specifically, if the oxygen atom layer is located between two silicon nanoparticles, the concentration of oxygen atoms is the highest at the center position of the connection line between the two silicon nanoparticles.

[0065] In the above-mentioned aggregate of silicon nanoparticles and heteroatoms, the heteroatoms separate the silicon nanoparticles and form strong chemical bonds with the silicon nanoparticles, and the silicon-based composite material has high mechanical strength and structural stability. More importantly, during the lithium insertion and expansion process of the silicon nanoparticles, the heteroatom layer can play a role in restricting the volume expansion of silicon, thereby reducing the expansion of the electrode sheet and improving the cycle stability of the battery.

[0066] Due to the strong mechanical strength and structural stability of the material, it is more likely to withstand pressure without damage. Therefore, the ratio of the compacted specific surface area of the silicon-based composite material to the specific surface area of the silicon-based composite material is relatively small. The compacted specific surface area is the specific surface area of the material after the silicon-based composite material is compacted under a pressure of 4000 kgf / cm 2 In some embodiments, the specific surface area of the silicon-based composite material is 0.5 - 50 m2 / g, preferably 0.5 to 10 m 2 / g, more preferably 0.5 to 2 m 2 / g; in some embodiments, the compacted specific surface area of ​​the silicon-based composite material is 1 to 20 times, preferably 1 to 10 times, and more preferably 1 to 5 times the specific surface area of ​​the silicon-based composite material.

[0067] [Coating layer]

[0068] In some embodiments, the above-mentioned silicon-based composite material also includes a coating layer, and the material of the coating layer is selected from a solid electrolyte (such as a LISICON-type solid electrolyte, a NASICION-type solid electrolyte, a perovskite-type solid electrolyte, a garnet-type solid electrolyte or a sulfide solid electrolyte), a conductive polymer (such as polyethylene oxide, carboxymethyl cellulose, polyacrylic acid or polyacrylonitrile), a carbonaceous material (such as carbon fiber, carbon nanotubes, graphite, graphene or amorphous carbon), a metal element or alloy (such as lithium, magnesium, copper, nickel, aluminum or silver and other metal elements), a metal oxide (such as aluminum oxide, zinc oxide, magnesium oxide, zirconium oxide or titanium oxide), a metal hydroxide, a metal halide, a metal sulfide, a metal phosphate, a boric acid compound, a sulfuric acid compound, a nitric acid compound, a polymetallic oxygen acid salt, etc. One or more; further preferably, the coating layer contains a carbonaceous material. B. Preparation method of silicon-based composite materials In the second typical embodiment of the present application, a preparation method of a silicon-based composite material is also provided, and the preparation method comprises: providing a porous matrix, the porous matrix having three-dimensional cross-channels with multi-level pore sizes; contacting a silicon-containing precursor and a heteroatom-containing precursor with the porous matrix, so that silicon nanoparticles and heteroatoms are filled in the channels of the porous matrix, wherein the heteroatoms are doped in the silicon nanoparticles or located between multiple silicon nanoparticles, and the above-mentioned porous matrix, channels, silicon nanoparticles and heteroatoms respectively have the same meanings as in the above-mentioned first typical embodiment, and will not be repeated here.

[0069] By applying the technical solution of the present application, in the preparation method of the silicon-based composite material provided by the present application, a silicon-containing precursor and a heteroatom-containing precursor are contacted with a porous matrix, and chemical vapor deposition is carried out in the pores of the porous matrix to form a collection of silicon nanoparticles and heteroatoms that are filled in the pores of the porous matrix. The silicon nanoparticles are separated and bound by doping heteroatoms between the silicon nanoparticles, and the size and distribution of the silicon material in the pores are controlled, so that the silicon material is uniformly dispersed in the three-dimensional cross-pores of the porous matrix, which effectively alleviates the volume effect of silicon during the charge and discharge process, prevents the expansion of silicon embedded with lithium and causes the collapse of the composite material structure, and improves the cycle stability of the electrode.

[0070] [Porous matrix and its pore structure]

[0071] In order to further improve and alleviate the volume effect of silicon during the discharge process, the porous matrix contains multi-level pores and has a multi-level pore distribution with a suitable ratio, which is conducive to the transport of materials and energy (heat) during the siliconization process and the formation of silicon nanoparticles of controllable size. In the first pore, the size of the silicon nanoparticles is relatively small, and the blocking of the pores by the silicon nanoparticles during the deposition process is conducive to the formation of an appropriate amount of closed pores, the expansion of silicon is alleviated, and the cycle performance is improved. However, if there are too many first pores (the volume of the first pore accounts for more than 95% of the pores), the silicon-containing precursor is easy to block the pore opening during the migration of the pores, and the silicon-containing precursor in the subsequent deposition process can no longer enter the pores for deposition, but deposits on the outer surface of the porous substrate, which will lead to two adverse consequences: i) A large number of pores exist in the final silicon-based composite material, the material strength is reduced, and the pole piece is easily crushed during the compaction process to form a large number of open pores, the specific surface area is increased, and the first effect is reduced; and the residual pores still cause the later material strength to decrease to form stress weak points during the cycle; ii) The surface of the material is rich in silicon, and larger silicon particles are formed on the surface, and the cycle stability is poor.

[0072] In the above preparation method, in the three-dimensional cross-channels of the porous matrix, a silicon nanoparticle and optional heteroatoms are filled in the first channel, and multiple silicon nanoparticles separated by heteroatoms are filled in the second channel and the optional third channel. The heteroatoms are arranged between the multiple silicon nanoparticles and partially or completely coated on the surface of the multiple silicon nanoparticles. Through the separation of heteroatoms, the size of the multiple silicon nanoparticles in the channel is smaller, avoiding the formation of larger silicon particles, and greatly improving the cycle stability of the composite electrode.

[0073] [Silicon-containing precursor]

[0074] The specific material of the silicon-containing precursor is not limited, and any material that can be used to deposit silicon atoms can be used, including but not limited to any one or a mixture of two or more of monosilane, disilane, trisilane, halosilanes, polysilanes, silole and its derivatives, silanol and its derivatives.

[0075] [Heteroatom-containing precursors]

[0076] The specific substances of the above heteroatom-containing precursors are not limited either, and any substances that can be used to deposit heteroatoms include but are not limited to any one of oxygen-containing precursors, carbon-containing precursors, nitrogen-containing precursors, phosphorus-containing precursors, sulfur-containing precursors or boron-containing precursors, or a mixture of at least two of the precursors. Among them, oxygen-containing precursors include but are not limited to O2, H2O, CO2, CO, O3, etc., carbon-containing precursors include but are not limited to methane, ethane, propane, butane, ethylene, propylene, butene, acetylene, propyne, etc.; nitrogen-containing precursors include but are not limited to inorganic nitrogen sources and / or nitrogen-containing organic matter (such as NH3, NO, N2O, acetonitrile); phosphorus-containing precursors include but are not limited to inorganic phosphorus sources and / or phosphorus-containing organic matter (such as PH3, POCl3), sulfur-containing precursors include sulfur-containing organic matter (such as H2S, SO2); boron-containing precursors include but are not limited to any one or a mixture of two or more of inorganic boron sources and / or boron-containing organic matter (such as B(CH3)3); it can also be a composite precursor such as a carbon-containing and oxygen-containing precursor, and the carbon-containing and oxygen-containing precursors include but are not limited to methanol, ethanol, n-propanol, isopropanol, butanol, acetone, butanone, etc.

[0077] [Chemical Vapor Deposition]

[0078] In some embodiments, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor contact the porous matrix is ​​150-1000°C (such as 150°C, 200°C, 300°C, 500°C, 600°C, 800°C, 1000°C, etc. or any temperature therebetween), and the time is 0.1-100h (such as 0.1h, 0.2h, 0.5h, 0.8h, 1h, 2h, 5h, 8h, 10h, 20h, 50h, etc. or any time therebetween); preferably, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor contact the porous matrix is ​​200-700°C. The manner in which the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous substrate and subjected to chemical vapor deposition can be various, mainly including three types: (1) the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous substrate alternately; (2) the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous substrate simultaneously; (3) the silicon-containing precursor and a mixed gas containing the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous substrate alternately. Preferably, the silicon-containing precursor is continuously contacted with the porous substrate, and the heteroatom-containing precursor is intermittently introduced during this process.

[0079] In some embodiments, the preparation method of the silicon-based composite material is carried out according to the following steps: step S1, providing a porous matrix, the porous matrix having three-dimensional cross channels with multi-level pore sizes, and placing the porous matrix in a furnace body; step S2, step S2-1, introducing a first mixed gas of a silicon-containing precursor and an inert gas into the furnace body, the volume concentration of the silicon-containing precursor in the first mixed gas is 1 to 50%, preferably 10 to 50%, and the temperature is maintained at 150 to 1000° C. for 0.5 to 15 hours, and the introduction of the silicon-containing precursor is stopped; step S2-2, introducing a second mixed gas of a heteroatom precursor and the inert gas into the furnace body, the volume concentration of the heteroatom precursor in the second mixed gas is 0.1 to 50%, preferably 0.1 to 10%, and the temperature is maintained at 150 to 1000° C. for 0.1 to 5 hours, and the introduction of the heteroatom precursor is stopped; repeating steps S2-1 and S2-2 in sequence for 2 to 50 times to obtain the silicon-based composite material.

[0080] In some embodiments, the preparation method of the silicon-based composite material is carried out according to the following steps: step S1, providing the porous matrix; placing the porous matrix in a furnace body; step S2, introducing a third mixed gas of a silicon-containing precursor, a heteroatom-containing precursor and an inert gas into the furnace body, wherein the volume concentration of the silicon-containing precursor in the third mixed gas is 1 to 50%, and the volume concentration of the heteroatom-containing precursor is 0.001 to 5%, maintaining the temperature at 150 to 1000° C. for 0.5 to 100 hours, and stopping the introduction of the heteroatom-containing precursor; cooling in the inert gas to obtain the silicon-based composite material.

[0081] In some embodiments, the preparation method of the silicon-based composite material is carried out according to the following steps: step S1, providing a porous matrix; placing the porous matrix in a furnace body; step S2, step S2-1, introducing a first mixed gas of a silicon-containing precursor and an inert gas into the furnace body, wherein the volume concentration of the silicon-containing precursor in the first mixed gas is 1 to 50%, and the temperature is maintained at 150 to 1000° C. for 0.5 to 15 hours, and the introduction of the silicon-containing precursor is stopped; step S2-2, introducing a third mixed gas of a silicon-containing precursor, a heteroatom-containing precursor and an inert gas into the furnace body, wherein the volume concentration of the silicon-containing precursor in the third mixed gas is 1 to 50%, and the volume concentration of the heteroatom-containing precursor is 0.001 to 5%, and the temperature is maintained at 150 to 1000° C. for 0.1 to 5 hours, and the introduction of the heteroatom-containing precursor is stopped; step S2-1 and step S2-2 are repeated 2 to 50 times in sequence to obtain a silicon-based composite material.

[0082] According to those skilled in the art, in the above steps S1 and S2, the porous matrix and / or the silicon-based composite material are crushed and classified. In some embodiments, the median particle size d of the obtained silicon-based composite material is V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / dV,50 is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.8~1.2.

[0083] In some embodiments, the preparation method further includes a step S3 arranged after step S2: coating the composite material obtained in step S2 to obtain a silicon-based composite material with a coating layer on the surface; preferably, the material of the coating layer is selected from one or more of solid electrolytes, conductive polymers, carbonaceous materials, metals, alloys, metal oxides, metal hydroxides, metal halides, metal sulfides, metal phosphates, boric acid compounds, sulfuric acid compounds, nitric acid compounds, polymetallic oxygen acid salts, etc.; further preferably, the coating layer contains carbonaceous materials.

[0084] C. Negative Electrode In the third typical embodiment of the present application, a negative electrode is further provided, comprising a negative electrode active material, wherein the negative electrode active material comprises any one of the silicon-based composite materials provided in the first typical embodiment or a silicon-based composite material obtained according to any one of the preparation methods provided in the second typical embodiment.

[0085] The negative electrode provided in the present application adopts the above-mentioned silicon-based composite material as the active material, which can effectively prevent the structural collapse caused by the expansion of silicon embedded in lithium and improve the cycle stability of the electrode. In the multi-level aperture channels of the porous matrix, silicon nanoparticles or a collection of silicon nanoparticles and heteroatoms are deposited, and the heteroatoms are arranged between the silicon nanoparticles. The strong Si-X bond (X is a heteroatom) can restrain the expansion of silicon embedded in lithium, or transfer the stress of silicon embedded in lithium to the surrounding space (such as the matrix, etc.), effectively controlling the volume expansion during the charge and discharge process. The porous matrix, as a base material, loads silicon nanoparticles and heteroatoms, which can also alleviate the expansion of silicon nanoparticles embedded in lithium to a certain extent. For example, a small amount of closed pores adjacent to silicon nanoparticles in the matrix can be used as a buffer space for volume expansion, thereby suppressing the expansion of the pole piece and further improving the cycle stability of the electrode.

[0086] D. Battery In the fourth typical embodiment of the present application, a lithium ion battery is also provided, which includes the negative electrode provided in the third typical embodiment. By adopting the above negative electrode, the electrical performance and cycle stability of the lithium ion battery are effectively improved, and it has broad application prospects.

[0087] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0088] Example 1

[0089] This embodiment provides a silicon-based composite material, which uses porous carbon as a porous matrix, on which silicon particles and heteroatoms are loaded, and the specific surface area of ​​the porous carbon is 1580 m 2 / g, pore volume is 0.70cm 3 / g, and the porous carbon has a three-dimensional cross channel with multi-level pore size, the channel includes a first channel and a second channel, wherein the pore size of the first channel is d1, 0.35nm≤d1≤2nm, and the volume accounts for 90%, and the pore size of the second channel is d2, 2nm<d2≤10nm, and the volume accounts for 10%, and the pore size distribution is as follows Figure 3 As shown; the silicon nanoparticles include first silicon nanoparticles and second silicon nanoparticles, the size of the first silicon nanoparticles is D1, 0.35nm≤D1≤2nm, the size of the second silicon nanoparticles is D2, 2nm<D2≤5nm, the first channel is filled with the first silicon nanoparticles, and the second channel is filled with the first silicon nanoparticles and / or the second silicon nanoparticles and oxygen atoms; the oxygen atoms are doped in the silicon nanoparticles in the second channel.

[0090] The silicon-based composite material is prepared according to the following steps:

[0091] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 5 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 200°C, the temperature was changed to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and the temperature was maintained at 200°C for 0.2 hours in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were carried out on the porous carbon in turn, and the cycle was repeated 3 times. The temperature was naturally lowered under the protection of N2, and a silicon-based composite material was obtained after crushing and grading. The silicon content, oxygen content, and d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 The silicon-based composite material provided in this embodiment was subjected to XRD test, and the obtained spectrum is as follows Figure 4 As shown, from Figure 4It can be seen that the nano-silicon-carbon composite material provided by the present application has no obvious crystallization peak at the Si crystallization peak position (2θ=28.4°), and is presented as a relatively wide peak package, indicating that the silicon nanoparticles dispersed in the pores of the porous matrix have extremely small particle sizes under the dual spacing of the porous matrix and heteroatoms, and are in or close to an amorphous state. The first cycle of the lithium removal curve of the pure half-cell specific capacity-voltage curve of Example 1 has no obvious platform in the voltage region of 0.4-0.5V; the lithium removal curve is subjected to capacity normalization, and the first-order differential of the voltage is performed by the normalized capacity, and the obtained dQ / dV spectrum is as follows Figure 5 As shown, it can be seen that the curve has no obvious peak in the 0.4-0.5V region, and the maximum dQ / dV value is 1.69; this is consistent with the fact that the half-cell specific capacity-voltage curve has no platform region in the voltage platform region. This result also shows that the silicon nanoparticles in the silicon-based composite material obtained in Example 1 have extremely small sizes. The silicon nanoparticles in the silicon-based composite material of Example 1 are bounded by the porous matrix and heteroatoms, and the structural strength of the material is greatly improved. 2 After compaction, its specific surface area only increased from the original 3.1m 2 / g increased to 12.5m 2 / g, showing high compressive strength and high structural stability during battery processing and cycling.

[0092] Comparative Example 1

[0093] The difference from Example 1 is that no heteroatoms are added during the siliconization process, and only the deposition of the silicon-containing precursor is performed, that is, the silicon deposition step is to place the porous carbon in an atmosphere furnace, raise the temperature from room temperature to 600°C at 2°C / min in an N2 atmosphere, and maintain it at 600°C for 5 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to perform silicon deposition; and after crushing and grading, a silicon-based composite material is obtained. The silicon content of the obtained silicon-based composite material is 51.3%, the oxygen content is 0.2%, and the d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0094] Figure 6 This is the dQ / dV spectrum corresponding to Comparative Example 1. It can be seen that, different from Example 1, there is an obvious peak at 0.4-0.5V in the dQ / dV spectrum of Comparative Example 1, and the maximum dQ / dV value reaches 2.25, which corresponds to a larger silicon nanoparticle size, indicating that under the same porous matrix conditions, silicon is infiltrated and the porous matrix contains mesopores. If heteroatom separation is not performed, larger silicon particles will be generated, which will ultimately lead to poor cyclic stability of the material.

[0095] Comparative Example 1 Silicon-based composite material was subjected to 4000kgf / cm 2 After compaction, its specific surface area increased from the original 3.4m 2 / g increased to 116m 2 / g, the material has poor compressive resistance and low structural stability during battery processing and cycling.

[0096] Example 2

[0097] This embodiment provides a silicon-based composite material. The difference between the silicon-based composite material and the embodiment 1 is that the porous carbon specific surface area is 1100m 2 / g, pore volume is 0.72cm 3 / g, and the porous carbon channel also includes a third channel, the pore size of the third channel is d3, 10nm<d3≤50nm; wherein the volume of the first channel accounts for 30%, the volume of the second channel accounts for 55%, and the volume of the third channel accounts for 15%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles. The silicon-based composite material is prepared according to the following steps:

[0098] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 1 hour in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 200°C, the temperature was changed to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and the temperature was maintained at 200°C for 0.1 hour in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were carried out on the porous carbon in turn, and the cycle was repeated 15 times. The temperature was naturally lowered under the protection of N2, and a silicon-based composite material was obtained after crushing and grading. The silicon content of the obtained silicon-based composite material is 51.5%, the oxygen content is 5.7%, and the d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0099] Example 3

[0100] This embodiment provides a silicon-based composite material. The difference between the silicon-based composite material and the embodiment 1 is that the porous carbon specific surface area is 1356m 2 / g, pore volume is 0.72cm 3 / g, and the pores of the porous carbon also include a third channel, the pore size of the third channel is d3, 10nm<d3≤50nm; wherein the volume of the first channel accounts for 90%, the volume of the second channel accounts for 1%, and the volume of the third channel accounts for 9%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles.

[0101] The silicon-based composite material is prepared according to the following steps:

[0102] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 3 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 200°C, the temperature was changed to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and the temperature was maintained at 200°C for 0.2 hours in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous carbon for 5 times in sequence, and the temperature was naturally lowered under the protection of N2. After crushing and grading, a silicon-based composite material was obtained. The silicon content, oxygen content, and d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0103] Example 4

[0104] This embodiment provides a silicon-based composite material. The difference between the silicon-based composite material and the embodiment 1 is that the porous carbon specific surface area is 305m 2 / g, pore volume is 0.25cm 3 / g, and the porous carbon channel also includes a third channel, the pore size of the third channel is d3, 10nm<d3≤50nm; wherein the volume of the first channel accounts for 36%, the volume of the second channel accounts for 60%, and the volume of the third channel accounts for 4%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles. The silicon-based composite material is prepared according to the following steps:

[0105] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 2 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 400°C, the temperature was changed to a second mixed gas of CO2 and N2 (the volume content of CO2 is 1%), and the temperature was maintained at 400°C for 0.2 hours in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous carbon for 3 times in sequence, and the temperature was naturally lowered under the protection of N2; the temperature was raised to 600°C in a N2 atmosphere, and the temperature was changed to 10% C2H2-N2 and maintained for 2 hours. A silicon-based composite material was obtained after crushing and grading. The silicon content, oxygen content, and d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0106] Example 5

[0107] This embodiment provides a silicon-based composite material. The difference between the silicon-based composite material and the embodiment 1 is that the porous carbon specific surface area is 1592m 2 / g, pore volume is 1.20cm 3 / g, and the porous carbon also includes a third channel, the pore size of the third channel is d3, 10nm<d3≤50nm; wherein the volume of the first channel accounts for 61%, the volume of the second channel accounts for 37%, and the volume of the third channel accounts for 2%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles. The silicon-based composite material is prepared according to the following steps:

[0108] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 2 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 200°C, the temperature was changed to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and the temperature was maintained at 200°C for 0.1 hour in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous carbon for 15 times in sequence, and the temperature was naturally lowered under the protection of N2. The silicon-based composite material was obtained after crushing and grading. The silicon content of the obtained silicon-based composite material is 81.2%, the oxygen content is 5.2%, and the d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50is 1.05.

[0109] Example 6

[0110] Commercial porous alumina is selected as the porous substrate material, and the specific surface area of ​​porous alumina is 675m 2 / g, pore volume is 0.52cm 3 / g, wherein the volume of the first channel accounts for 50%, the volume of the second channel accounts for 40%, and the volume of the third channel accounts for 10%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles.

[0111] The silicon-based composite material is prepared according to the following steps:

[0112] The porous alumina was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 2 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 200°C, the temperature was changed to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and the temperature was maintained at 200°C for 0.1 hour in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous alumina for 5 times in sequence; the temperature was raised to 600°C in a N2 atmosphere, and the temperature was changed to 10% C2H2-N2 and maintained for 2 hours. After crushing and grading, a silicon-based composite material was obtained. The silicon content of the obtained silicon-based composite material was 48.2%, the total oxygen content was 23.5%, and the d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0113] Example 7

[0114] Commercial silicoaluminophosphate molecular sieve SAPO-18 is selected as the porous substrate material. The specific surface area of ​​silicoaluminophosphate molecular sieve is 722m 2 / g, pore volume is 0.71cm 3 / g, wherein the volume of the first channel accounts for 42%, the volume of the second channel accounts for 52%, and the volume of the third channel accounts for 6%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles.

[0115] Place the silicoaluminophosphate molecular sieve in an atmosphere furnace, heat it from room temperature to 600°C at 2°C / min in a N2 atmosphere, and keep it at 600°C for 2 hours in an atmosphere of the first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition, then stop introducing SiH4 and introduce only N2. After cooling to 200°C, change to the second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), and keep it at 200°C for 0.1 hour in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition are cycled on porous alumina for 6 times in sequence; heat it to 600°C in a N2 atmosphere, change to 10% C2H2-N2, and keep it for 2 hours. After crushing and grading, a silicon-based composite material is obtained. The silicon content of the obtained silicon-based composite material is 51.3%, the total oxygen content is 21.2%, and the d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0116] Example 8

[0117] The oxygen deposition in Example 1 was changed to nitrogen deposition, the second mixed gas was changed to a 0.1% NH3-N2 mixed gas, the nitrogen deposition temperature was 400°C, and the remaining steps were the same as in Example 1 to obtain an N-doped silicon-based composite material.

[0118] Example 9

[0119] The oxygen deposition in Example 1 was changed to phosphorus deposition, the second mixed gas was changed to a 0.1% PH3-N2 mixed gas, the temperature of phosphorus deposition was 400°C, and the remaining steps were the same as in Example 1 to obtain a P-doped silicon-based composite material.

[0120] Example 10

[0121] The oxygen deposition in Example 1 is changed to boron deposition, the second mixed gas is changed to a 0.05% B(CH3)3-N2 mixed gas, the temperature of boron deposition is 400°C, and the remaining steps are the same as Example 1 to obtain a B-doped silicon-based composite material.

[0122] Embodiment 11

[0123] The difference between this embodiment and embodiment 1 is that C2H2 chemical vapor deposition is performed on the silicon-based composite material obtained in embodiment 1 to form a carbon coating layer on its surface. The thickness of the carbon coating layer is 10 nm, thereby obtaining a carbon-coated silicon-based composite material.

[0124] Example 12

[0125] The difference between this embodiment and embodiment 1 is that a LiPO3 coating layer is formed on the surface of the silicon-based composite material obtained in embodiment 1, and the thickness of the LiPO3 coating layer is 5 nm, thereby obtaining a silicon-based composite material. The specific step of coating is to mix the silicon-based composite material obtained in embodiment 1 with a LiPO3 solution, wherein the mass ratio of the silicon-based composite material to LiPO3 is 100 / 1, and spray-dry to obtain a silicon-based composite material coated with LiPO3.

[0126] Embodiment 13

[0127] This embodiment provides a silicon-based composite material. The difference between the silicon-based composite material and the embodiment 1 is that the porous carbon specific surface area is 221m 2 / g, pore volume is 0.62cm 3 / g, the volume of the first channel accounts for 10%, the volume of the second channel accounts for 38%, and the volume of the third channel accounts for 52%; the first channel is filled with first silicon nanoparticles, and the second channel and the third channel are respectively filled with at least one of the first silicon nanoparticles, the second silicon nanoparticles, and the third silicon nanoparticles. The silicon-based composite material is prepared according to the following steps:

[0128] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 0.5h in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition, and then the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 400°C, the temperature was changed to a second mixed gas of CO2 and N2 (the volume content of CO2 is 0.1%), and the temperature was maintained at 400°C for 0.1h in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous carbon for 30 times in sequence, and the temperature was naturally lowered under the protection of N2; the temperature was raised to 600°C in a N2 atmosphere, and the temperature was changed to 10% C2H2-N2 and maintained for 2h. A silicon-based composite material was obtained after crushing and grading. The silicon content, oxygen content, and d V,50 8μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 1.05.

[0129] Test Example 1

[0130] The specific surface area of ​​the porous matrix in Examples 1 to 14 and Comparative Example 1 was calculated according to multi-point BET, the total pore volume (total pore volume) was calculated according to the adsorption amount at the maximum partial pressure (p / p0>0.99), the N2 adsorption-desorption isotherm was fit using the DFT method, the pore distribution of the first pore channel, the second pore channel, and the third pore channel of the porous matrix was analyzed, and the content information of each level of pore size was obtained. The results are presented in each embodiment.

[0131] Test Example 2

[0132] The true density of the silicon-based composite materials provided in the examples and comparative examples was tested by helium pycnometry. The results are shown in Table 2.

[0133] Test Example 3

[0134] The volume of closed pores is inferred from the true density of the composite material obtained by the helium specific gravity method. When the true density of the material is less than the true density (theoretical density) of a completely dense material with the same elemental composition, it indicates the presence of closed pores. The closed pore volume is the reciprocal of the true density of the composite material (closed pore volume + dense volume) minus the reciprocal of the true density of a completely dense material with the same elemental composition (dense volume). The results are shown in Table 2 below.

[0135] Test Example 4

[0136] Compacted specific surface area: Powder was placed into a 12 mm diameter mold and subjected to 4000 kgf / cm 2 The pressure is maintained for 30 seconds, and the specific surface area of ​​the compacted material is tested and recorded as the compacted specific surface area. The smaller the ratio of the compacted specific surface area to the specific surface area, the stronger the compressive resistance of the material.

[0137] Test Example 5

[0138] Electrode, half-cell preparation and electrochemical performance testing:

[0139] The silicon-based composite materials provided in the above examples and comparative examples were used as negative electrode active materials to prepare negative electrode sheets, and the negative electrode sheets were used to prepare CR2032 button batteries using conventional methods, and the batteries were tested for electrical properties. The results are shown in Table 3, and the specific test methods are as follows:

[0140] (1) Half-cell assembly: CR2032 button cells were assembled in a glove box, with lithium metal sheets as counter electrodes, polypropylene microporous membranes as separators, and the electrolyte being LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC = 1:1), where the LiPF6 concentration was 1 mol / L.

[0141] The battery is charged and discharged using the LAND battery testing system.

[0142] (2) Cyclic gram capacity and first efficiency test: After the CR2032 battery is left uncharged for 6 hours, it is discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V; after standing for 5 minutes, it is charged to 1.5V at 0.05C constant current; the first lithium removal gram capacity is the gram capacity (or mass specific capacity) of the electrode material, and the ratio of the first lithium removal capacity to the first lithium insertion capacity is the first coulombic efficiency of the battery.

[0143] Test Example 6

[0144] Full battery preparation and electrochemical performance testing:

[0145] The silicon-based composite materials provided in the above embodiments and comparative examples were used as negative electrode active materials. The pole pieces containing the negative electrode active materials were prepared into soft-pack batteries by conventional methods and the electrical performance tests were performed. The soft-pack batteries were prepared in a dehumidification room with a dew point of -45°C. The battery was tested for charge and discharge cycles using a LANBTS battery testing system. The results are shown in Table 3. The specific testing method is as follows:

[0146] (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, the conductive agent SuperP, the binder PVDF and the solvent NMP were stirred and mixed in a mass ratio of 92:3:5:150, and then evenly coated on the positive electrode collector, and then dried at 80°C to obtain the positive electrode sheet.

[0147] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent SuperP, binder polyacrylic acid and solvent deionized water were stirred and mixed in a mass ratio of 95:1:4:120, and then evenly coated on the negative electrode collector, and then dried at 100°C to obtain the negative electrode sheet.

[0148] (3) The positive electrode sheet and the negative electrode sheet are stacked in a square shape and separated by a polypropylene separator to form a battery core, which is then packaged into an aluminum-plastic bag. An electrolyte with a corresponding capacity is injected into the aluminum-plastic bag, and the bag is vacuum-sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6, EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1. (4) Formation: After the battery is filled and sealed, it begins to form, and is placed in a 25°C constant temperature box for 12 hours. It is then charged to 3.3V at 0.02C constant current, placed for 30 minutes, charged to 3.8V at 0.025C constant current, placed for 10 minutes, and charged to 4.2V at 0.33C constant current. The formed battery is vacuumed and the air bag is cut, and then the capacity is divided. It is charged to 4.45V at 0.33C constant current, placed for 10 minutes, discharged to 3V at 1C constant current, placed for 10 minutes, and discharged to 3V at 0.33C constant current. The capacity division is completed. The ratio of the discharge capacity divided by the charge capacity in the soft pack battery formation is the battery's first efficiency.

[0149] (5) 25℃ cycle test: The battery was placed in a 25℃ constant temperature box, charged to 4.45V at 1C constant current, and then charged to 0.1C at 4.45V constant voltage; after standing for 10 minutes, discharged to 3.0V at 1C constant current, and stood for 10 minutes. The above charging and discharging steps were repeated until the discharge capacity was lower than 80% of the first cycle discharge capacity. The number of cycles obtained at this time is the cycle life of the soft-pack battery; the capacity retention rate after 100 cycles was recorded.

[0150] (6) 45°C cycle test: The battery was placed in a 45°C thermostat, and the other steps were the same as the 25°C cycle test. The test results of Test Examples 2 to 6 are shown in Tables 1 and 2 below.

[0151] Table 1

[0152]

[0153] Table 2

[0154]

[0155] From the data in Table 1 and Table 2, it can be seen that compared with Comparative Example 1, the silicon-carbon composite materials obtained in Examples 1 to 13 of the present invention show higher compressive strength and higher cycle stability in lithium-ion battery applications. Examples 1 to 5 are silicon-based composite materials obtained after siliconization of porous carbon substrates with different pore distributions. The silicon content is related to the total pore volume of the porous substrate, and thus the materials show different specific capacities and first effects. Examples 6 and 7 use porous oxides as the matrix, and the matrix material has a higher true density and compressive strength, so the composite material also shows a higher true density and compressive strength; but on the other hand, since the matrix material has a higher oxygen content, carbon coating is required during the preparation process to enhance conductivity. In battery applications, the first coulomb efficiency is also reduced due to the high oxygen content; if the first coulomb efficiency of the material needs to be improved, the composite material needs to be pre-lithiated. Examples 8 to 10 are silicon-based composite materials obtained by doping with different elements, which also show better electrochemical properties. Examples 11 to 12 are silicon-based composite materials with a carbon layer or an ion conductor layer coated on the surface. Because of the protection of the coating layer, the expansion of silicon particles is further suppressed, and the 100-cycle capacity retention rate reaches 98.7% and 98.8% respectively. Example 13 The volume proportion of the first pore channel is too low. If pure silicon is directly deposited without heteroatom restriction, the size of the silicon nanoparticles in the obtained composite material will exceed 5nm or even 10nm, and the cycle stability in the lithium-ion battery will be greatly reduced; but in this application, multiple oxygen atom depositions are used between silicon nanoparticles, and the obtained silicon-based composite material still shows good cycle stability. It can be seen that the silicon-based composite material provided by the present invention sets multi-level aperture channels and the proportion of aperture channels at each level on the porous substrate, and separates the silicon nanoparticles by heteroatom deposition during the deposition process, effectively controlling the size and distribution of silicon particles, thereby limiting the silicon expansion to a smaller range, so that the obtained silicon-based composite material has higher cycle stability.

[0156] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicon-based composite material, characterized in that: The silicon-based composite material comprises silicon-based composite material particles, wherein the silicon-based composite material particles include a porous matrix, silicon nanoparticles and heteroatoms, wherein the porous matrix has three-dimensional cross-channels with multi-level pore sizes, wherein the channels contain at least one silicon nanoparticle, and the heteroatoms are at least partially coated on the surface of the silicon nanoparticles, and / or the heteroatoms are spaced between the silicon nanoparticles.

2. The silicon-based composite material according to claim 1, characterized in that: The silicon-based composite material also contains closed pores, and the closed pore volume of the silicon-based composite material is 0.01 to 0.25 cm 3 / g; and / or, the true density of the silicon-based composite material is 1.3 to 3.0 g / cm 3 .

3. The silicon-based composite material according to claim 1, characterized in that: The specific surface area of ​​the silicon-based composite material is 0.5 to 50 m 2 / g, preferably 0.5 to 10 m 2 / g, more preferably 0.5 to 2 m 2 / g; and / or, the compacted specific surface area of ​​the silicon-based composite material is 1 to 20 times, preferably 1 to 10 times, and more preferably 1 to 5 times the specific surface area of ​​the silicon-based composite material.

4. The silicon-based composite material according to claim 1, characterized in that: The silicon nanoparticles include first silicon nanoparticles, second silicon nanoparticles and third silicon nanoparticles, the size of the first silicon nanoparticles is D1, 0.35nm≤D1≤2nm, the size of the second silicon nanoparticles is D2, 2nm<D2≤5nm, and the size of the third silicon nanoparticles is D3, 5nm<D3≤10nm; Preferably, based on the mass of the silicon nanoparticles, the mass content of the first silicon nanoparticles is 60-100%, the mass content of the second silicon nanoparticles is 0-40%, and the mass content of the third silicon nanoparticles is 0-5%.

5. The silicon-based composite material according to claim 1, characterized in that: The pores of the porous matrix include a first pore, a second pore and a third pore, the pore size of the first pore is d1, 0.35nm≤d1≤2nm, the pore size of the second pore is d2, 2nm<d2≤10nm, and the pore size of the third pore is d3, 10nm<d3≤50nm; Preferably, the volume proportion of the first pores in the porous matrix pores is 30-95%, the volume proportion of the second pores in the porous matrix pores is 1-60%, and the volume proportion of the third pores in the porous matrix pores is 0-15%.

6. The silicon-based composite material according to claim 1, characterized in that: The porous matrix includes at least one of porous carbon, molecular sieve, porous metal, porous metal oxide, porous metal organic framework, and porous organic-inorganic hybrid material framework; preferably, the specific surface area of ​​the porous matrix is ​​200 to 3000 m 2 / g, pore volume is 0.2~3.0cm 3 / g.

7. The silicon-based composite material according to claim 1, characterized in that: In the silicon-based composite material, the mass content of the silicon element is 5 to 90%, and the mass content of the heteroatom is 0.1 to 10%; And / or, the heteroatom is coated on the surface of the silicon nanoparticle and / or is spaced between a plurality of the silicon nanoparticles to form a heteroatom layer, wherein the total thickness of the heteroatom layer is 0.5 to 50 nm, preferably 0.5 to 10 nm, and more preferably 0.5 to 2 nm; And / or, the heteroatom includes at least one of B, C, N, P, O, and S.

8. The silicon-based composite material according to claim 1, characterized in that: The median particle size d of the silicon-based composite material V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.8~1.

2.

9. The silicon-based composite material according to any one of claims 1 to 8, characterized in that: The silicon-based composite material also includes a coating layer; preferably, the material of the coating layer is selected from one or more of solid electrolytes, conductive polymers, carbonaceous materials, metals, alloys, metal oxides, metal hydroxides, metal halides, metal sulfides, metal phosphates, boric acid compounds, sulfuric acid compounds, nitric acid compounds, polymetallic oxygen acid salts, etc.; further preferably, the coating layer contains carbonaceous materials.

10. A method for preparing a silicon-based composite material, characterized in that: The preparation method comprises: step S1, providing a porous matrix, wherein the porous matrix has three-dimensional cross-channels with multi-level pore sizes; step S2, contacting a silicon-containing precursor and a heteroatom-containing precursor with the porous matrix to obtain the silicon-based composite material; Wherein, the porous matrix, the pores, the silicon nanoparticles and the heteroatoms have the same meanings as the porous matrix, the pores, the silicon nanoparticles and the heteroatoms in claims 1 to 9, respectively.

11. The preparation method according to claim 10, characterized in that: In the step S2, the silicon-containing precursor includes at least one of monosilane, disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives; and / or, the heteroatom-containing precursor comprises at least one of an oxygen-containing precursor, a carbon-containing precursor, a nitrogen-containing precursor, a phosphorus-containing precursor, a sulfur-containing precursor or a boron-containing precursor; And / or, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor are in contact with the porous matrix is ​​150-1000° C., and the time is 0.1-100 h; preferably, the temperature at which the silicon-containing precursor and the heteroatom-containing precursor are in contact with the porous matrix is ​​200-700° C.; And / or, the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix in the following manners: the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix alternately; or, the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix simultaneously; or, the silicon-containing precursor and a mixed gas comprising the silicon-containing precursor and the heteroatom-containing precursor are contacted with the porous matrix alternately. Preferably, the silicon-containing precursor is continuously contacted with the porous matrix, and the heteroatom-containing precursor is intermittently introduced during this process.

12. The preparation method according to claim 10, characterized in that: The preparation method further comprises a step S3 arranged after the step S2: coating the composite material obtained in the step S2 to obtain a silicon-based composite material having a coating layer on the surface; The coating layer has the same meaning as the coating layer in claim 9.

13. A negative electrode, characterized in that The negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the silicon-based composite material according to any one of claims 1 to 9 or the silicon-based composite material obtained by the preparation method according to any one of claims 10 to 12.

14. A battery, characterized in that The battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, the negative electrode comprises a negative electrode active material, the negative electrode active material comprises the silicon-based negative electrode material containing sub-nano pores according to any one of claims 1 to 9, and / or the silicon-based negative electrode material containing sub-nano pores obtained by the preparation method according to any one of claims 10 to 12.

Citation Information

Patent Citations

  • Novel materials with extremely durable lithium intercalation and their manufacturing method

    CN108475779B

  • Electroactive materials for metal ion batteries

    CN114342115A

  • Nano silicon-oxygen-carbon composite material as well as preparation method and application thereof

    CN116525776A

  • KR20220075740A

Cited By

  • Carbon material, silicon-carbon composite material and application thereof

    CN120057919A

  • Silicon-based composite material and preparation method therefor, and negative electrode

    EP4773224A1

  • Silicon-based composite material and preparation method therefor, and negative electrode

    WO2025050621A1